Observation of respiration-entrained brain oscillations with scalp EEG - Watanabe, Tatsunori; Itagaki, Atsunori; Hashizume, Akira; Takahashi, Aoki; Ishizaka, Riku; Ozaki, Isamu (Neuroscience letters, 2023)
•Nasal respiration entrains oscillations in several brain regions.•The presence of respiration-entrained oscillations was examined with scalp EEG.•There was significant coherence between scalp EEG and respiration signals.•Scalp EEG can detect respiration-entrained oscillations. In animal models, oscillations of local field potentials are entrained by nasal respiration at the frequency of breathing cycle in olfactory brain regions, such as the olfactory bulb and piriform cortex, as well as in the other brain regions. Studies in humans also confirmed these respiration-entrained oscillations in several brain regions using intracranial electroencephalogram (EEG). Here we extend these findings by analyzing coherence between cortical activity and respiration using high-density scalp EEG in twenty-seven healthy human subjects. Results indicated the occurrence of significant coherence between scalp EEG and respiration signals, although the number and locations of electrodes showing significant coherence were different among subjects. These findings suggest that scalp EEG can detect respiration-entrained oscillations. It remained to be determined whether these oscillations are volume conducted from the olfactory brain regions or reflect the local cortical activity.